Aspectual Inquiries - Kempchinsky, Paula; Slabakova, Roumyana; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The study of the linguistic reflexes of aspect has been an active field of research in various sub-disciplines of linguistics, such as syntax, semantics (including discourse theory) and acquisition studies. However, communication and dissemination of results across these various subfields has often been indirect. The different angles brought together give us a comprehensive picture of the representation of aspect in the mind/brain of the speaker. The papers in this volume represent the results of a workshop on the syntax, semantics and acquisition of aspect held in 2002 whose purpose was to foment active cross-disciplinary communication. A number of the papers examine the syntactic representation of lexical or situation aspect, while others focus on the syntactic interaction of lexical aspect with grammatical aspect, and of grammatical aspect and tense. Other papers examine the role of aspect in discourse representations, while a third group of papers reports on results of empirical studies on the acquisition of aspect in both first and second language acquisition, and patterns of loss of morphosyntactic reflexes of aspect in language attrition.
Issues and Interfaces in the Study of Aspect -- Aspect and the Internal Structure of the Clause -- Topic or Aspect -- Some Notes on the Syntax of Quantity -- Articulated vPS and the Computation of Aspectual Classes -- Flavors of v -- Semi-Copulas -- PP, FP and the Telic/Atelic Distinction in Norwegian Motion Constructions -- Aspect, Tense and Discourse -- The Spatio-Temporal Path and Aspectual Composition -- Aspect and Temporal Modification -- Aspectual Entities and Tense in Discourse -- Stage Structure and Stage Salience for Event Semantics -- Aspectual Viewpoints, Speech Act Functions and Discourse Structure -- Aspect and Acquisition -- Child Non-Finite Clauses and the Mood-Aspect Connection -- Imperfect Imperfectives -- L2 Acquisition of Aspectual Distinctions in Polish -- Aspect Lost, Aspect Regained -- Tracking the Elusive Imperfect in Adult L2 Acquisition.
Keywords: Linguistics; Philosophy; Language and languages -- Philosophy; Psycholinguistics; Semantics; Syntax; Linguistics; Linguistics, general; Philosophy, general; Semantics; Syntax; Psycholinguistics; Philosophy of Language; Electronic books